Perencanaan dan Pengendalian Proyek dengan Metode Pert - CPM Studi Kasus : Fly Over Ahmad Yani â€“ Karawang - A, Anggara Hayun (Journal the Winners: Economics, Business, Management, and Information System Journal, 2005)
The efficiency and effectivity is not a new guide in this global era. As aÂ professional and innovative company, like consultant construction company that alwaysÂ makes customer satisfy, has a good achievement and reputation. There fore, efficiencyÂ and affectivity are necessary needed in a company. Article gives some inputs how toÂ manage time become more effective and efficient in finishing project with CPM method.Â With using CPM method in â€œfly over project Ahmad Yani-Karawangâ€, is figured out theÂ optimal time to finish this project which is 184 days.Keywords:Â